PENGEMBANGAN KOMIK BUDAYA ”TONḌU’ MAJÂNG” SEBAGAI MEDIA PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Amalia, Riska; Sari, Tita Tanjung; Kadarisman, Kadarisman (Jurnal Muassis Pendidikan Dasar, 2024)
Cultural comics are one of the alternative reading materials to increase students' knowledge of learning related to the socio-cultural environment in the neighborhood. This study aims to develop media in the form  of cultural comics "Tonḍu' Majâng" that are interesting and educational for grade IV elementary school students to introduce the culture around the residence, especially the culture on Madura Island and find out the response of teachers and students after using this comic media. This research uses a research development approach or Research and Development (R & D) with a 4-D model proposed by tiagharajan, namely define, design, develop and disseminate. The creation of cultural comics "Tonḍu' Majâng" uses applications in the form of canva, mediabangpaint and photoshop. This research involved 2 validators, namely material expert validators and media expert validators and conducted 2 trials consisting of limited trials with 5 research subjects and free trials with 8 research subjects. The results of this study showed that: (1) material validation resulted in scores with an average percentage of 98.5% and media validation with an average percentage of 92.5% and teacher responses with an average assessment of 89.5% and student responses during limited trials resulted in an average score of 88% and free trials produced an average percentage score of 96%. Therefore, the development of cultural comics is suitable for use in the learning process of grade IV Social Science material